2004
DOI: 10.1002/mnfr.200400035
|View full text |Cite
|
Sign up to set email alerts
|

Expression profiles of effector proteins SopB, SopD1, SopE1, and AvrA differ with systemic, enteric, and epidemic strains of Salmonella enterica

Abstract: The presence and expression of sopB, sopD1, sopE1, and avrA genes encoding virulence associated effector proteins were studied comparatively in 405 Salmonella enterica strains. They belong to different serovars and clonal types (genotypes, phage types) and originated from different clinical (systemic infection, focal enteritis, enterocolitis) and epidemic sources (epidemics, sporadic cases). The sopB and sopD1 determinants were commonly prevalent, but sopE1 and avrA genes only in 55% and 80%, respectively. A c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
44
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 39 publications
(37 reference statements)
6
44
0
Order By: Relevance
“…The results from this study are in agreement with Streckel et al (2004) and Hughes et al (2008) who found a low prevalence of the sopE gene in S. enterica. SopE is encoded by a P2-like cryptic bacteriophage (SopEA) (Hardt et al 1998).…”
Section: Wandsworth Wa 1(m) Wa 2(m) Wa 3 (M)supporting
confidence: 95%
“…The results from this study are in agreement with Streckel et al (2004) and Hughes et al (2008) who found a low prevalence of the sopE gene in S. enterica. SopE is encoded by a P2-like cryptic bacteriophage (SopEA) (Hardt et al 1998).…”
Section: Wandsworth Wa 1(m) Wa 2(m) Wa 3 (M)supporting
confidence: 95%
“…The whole avrA gene plus 300 nt downstream were sequenced in strain SSM 3215, confirming the correct fusion of the ORF with the 36FLAG coding sequence. It is worth pointing out here that the avrA gene is present in approximately 80 % of S. enterica serovars, although few of them synthesize the effector (Streckel et al, 2004).…”
Section: Epitope Tagging Does Not Affect the Invasive Ability Of Seromentioning
confidence: 90%
“…Interestingly, the avrA gene is prevalent in the majority of S. enterica serovars; however, only a small number of them usually produce the protein (Streckel et al, 2004). Ben-Barak et al (2006) have demonstrated that avrA expression is dependent on a specific regulatory function which appears to be differently modulated in the distinct Salmonella serovars.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently studies showed that the AvrA gene is present in 80% of Salmonella enterica serovar. 1 Although its exact function is not entirely clear, AvrA belongs to the family of cysteine proteases regulating diverse bacterialhost interactions. 2 Other family members related to AvrA include the adenovirus protease AVP, Yersinia virulence factor YopJ (Yersinia outer protein J), and the Xanthomonas campestris pv.…”
mentioning
confidence: 99%